Analysis of Nova 1 strategy formed by barrier options and its application in hedging against a price drop in oil market - Michal Šoltés; Monika Harčariková (Acta Montanistica Slovaca, 2015)
This paper investigates hedging analysis against an underlying price drop by using the Nova 1 strategy formed by standard vanilla and barrier options. There are used European down and knock-in put options together with barrier call options. Derived income functions from the secured positions in analytical expressions are presented. Based on the theoretical results, the hedged portfolio is applied to SPDR SandP Oil and Gas Exploration and Production ETF. The proposed hedging variants are analysed and compared with the recommendation of the best possibilities for investors.